The tolerance of English instructors towards the Thai-accented English and grammatical errors - Osatananda, Varisa; Salarat, Parichart (Indonesian Journal of Applied Linguistics, 2020)
Saraceni 2015), it has not been enthusiastically embraced by Thai educators, as evidenced in the frustration expressed by ELT practitioners over Thai learners’ difficulties with pronunciation (Noom-ura 2013; Sahatsathatsana, 2017) as well as grammar (Saengboon 2017a). In this study, we examine the perception English instructors have on the different degrees of grammar skills and Thai-oriented English accent. We investigated the acceptability and comprehensibility of both native-Thai and native-English instructors (ten of each), as these subjects listen to controlled passages produced by 4 Thai-English bilingual speakers and another 4 native-Thai speakers. There were 3 types of passage tokens: passages with correct grammar spoken in a near-native English accent, passages with several grammatical mistakes spoken in a near-native English accent, and the last being a Thai-influenced accent with correct grammar. We hypothesized that (1) native-Thai instructors would favor the near-native English accent over correct grammar, (2) native-English instructors would be more sensitive to grammar than a foreign accent, and (3) there is a correlation between acceptability and comprehensibility judgment. The findings conformed to the first hypothesis, given that most Thai instructors were tolerant towards the near-native English accent, regardless of grammatical errors. The second hypothesis is rejected since native-English instructors were less tolerant of both grammatical errors and foreign accents. The third hypothesis was proved correct that acceptability correlates with comprehensibility. Our study suggests that English instructors should devote proportionate attention to teaching both pronunciation and grammar. They should also be made aware of the negative attitude against Thai-accented English so that learners would be treated fairly and without discrimination based on their Thai-influenced accent.